Assessment of Groundwater Quality in Gramthan Rural Municipality of Morang District, Nepal - Das, Bishnu Dev; Bhagat, Indramani; Sardar, Amrita; Pradhan, Sonu (Himalayan Journal of Science and Technology, 2024)
This study assesses the groundwater quality in Gramthan Rural Municipality, Morang District, Nepal, with the aim of evaluating its suitability for drinking purposes. Fifteen groundwater samples were analyzed for physicochemical parameters, including temperature, pH, dissolved oxygen (DO), nitrate (NO₃⁻), nitrite (NO₂⁻), ammonium (NH₄⁺), arsenic (As), iron (Fe), phosphate (PO₄³⁻), total dissolved solids (TDS), total alkalinity (TA), and well depth. The results showed that most parameters were within permissible limits set by the World Health Organization (WHO), except for dissolved oxygen and iron, which were below and above the recommended thresholds, respectively, in several samples. Iron concentrations reached up to 1.5 mg/L, exceeding the WHO guideline of 0.3 mg/L. Additionally, microbial analysis revealed fecal coliform contamination in several samples, with the highest recorded value being 22 MPN/100 mL, surpassing safe drinking water limits. The presence of coliform bacteria is likely linked to poor sanitation practices, such as the absence of a concrete base around wells and proximity to contamination sources. These findings highlight the potential health risks associated with groundwater consumption in the study area and underscore the need for improved water management and sanitation infrastructure to ensure public health safety.